Passivation layer, perovskite solar cell comprising passivation layer, and preparation method and application of passivation layer
By spin-coating a passivator solution composed of 2,2-bipyridine on the surface of the perovskite solar cell thin film, a stable passivation layer is formed, which solves the problem of interface structure defects in the film surface and significantly improves the performance and stability of the solar cell.
Patent Information
- Application Number
- CN202411690414.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
Smart Images

Figure CN119584762A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photoelectric material preparation, and in particular to a passivation layer, a perovskite solar cell comprising the passivation layer, and a preparation method and application thereof. Background Art
[0002] At present, the highest certified photoelectric conversion efficiency of organic-inorganic lead halide perovskite solar cells (PSCs) exceeds that of commercialized polycrystalline silicon and inorganic compound thin film solar cells. The charge recombination loss inside the perovskite film grains prepared based on current technology is almost negligible. However, a series of studies have shown that the defect state density of polycrystalline perovskite films is still several orders of magnitude higher than that of single crystal perovskites. The main reason is that there are unavoidable uncoordinated Pb at the surface interface of polycrystalline perovskite films. 2+ These defect sites not only capture photogenerated carriers, causing energy loss, but also easily absorb substances such as water vapor and oxygen in the environment, accelerating the degradation process of perovskite films. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0004] To this end, embodiments of the present invention provide a passivation layer, a perovskite solar cell comprising the passivation layer, and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a passivation layer, wherein the passivation layer is formed by spin coating a passivation agent solution, wherein the passivation agent solution comprises a passivation agent and an organic solvent, and wherein the passivation agent is 2,2-bipyridine.
[0006] Furthermore, the organic solvent is chlorobenzene.
[0007] Furthermore, the mass volume ratio of the passivating agent to the organic solvent is (1-6) mg:1 mL.
[0008] Furthermore, the spin coating has a rotation speed of 2000-4000 rpm and a time of 10-30 s.
[0009] In a second aspect, the present invention proposes a perovskite solar cell comprising the passivation layer proposed in the first aspect, comprising a passivation layer, wherein the passivation layer is spin-coated on the light absorbing layer.
[0010] Furthermore, the light absorbing layer is formed by a light absorbing layer precursor solution, and the light absorbing layer precursor solution includes PbI 2 powder, MAI powder, dimethyl sulfoxide and organic solvent.
[0011] Furthermore, the light absorbing layer precursor solution also includes DMAI powder.
[0012] In a third aspect, the present invention proposes a method for preparing a perovskite solar cell including the passivation layer proposed in the first aspect or the perovskite solar cell proposed in the second aspect, comprising the following steps: spin coating a passivation agent solution on the light absorbing layer, and annealing to obtain a passivation layer.
[0013] Furthermore, the annealing time is 80-100° C. and the annealing time is 15-20 min.
[0014] In a fourth aspect, the present invention proposes the use of a perovskite solar cell comprising the passivation layer proposed in the first aspect, or a perovskite solar cell proposed in the second aspect, or a perovskite solar cell prepared by the method proposed in the third aspect in rooftop photovoltaic systems and outdoor mobile devices.
[0015] Compared with the prior art, the beneficial effects of the present invention are:
[0016] In the present invention, the two N atoms on the two pyridine rings in 2,2-bipyridine can simultaneously react with the metal ion Pb 2+ Coordination to form a stable chelate structure can achieve the simultaneous improvement of passivation effect and passivation stability, and improve the performance of perovskite solar cells such as open circuit voltage Voc, short circuit current Jsc, fill factor FF and photoelectric conversion efficiency PCE. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0018] Figure 1 This is a schematic diagram of a scanning electron microscope after a passivation layer is formed in Example 1 of the present invention;
[0019] Figure 2 This is a schematic diagram of a scanning electron microscope after forming a light absorbing layer in Comparative Example 1. DETAILED DESCRIPTION
[0020] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0021] Example 1
[0022] Prepare FTO glass with 80nm nickel oxide hole transport layer deposited on it and move it into the glove box for later use.
[0023] 2535.5 mg of PbI 2Powder, 874.4 mg of MAI powder and 429.7 mg of dimethyl sulfoxide were dissolved in 3.5 mL of DMF and stirred for 12 min; filtered using a 0.22 μm polyethersulfone filter membrane to obtain an absorbing layer precursor solution and aged it at 60° C. for 2 h to obtain an aged absorbing layer precursor solution.
[0024] The aged light absorbing layer precursor solution is spin-coated on the FTO glass deposited with the hole transport layer, and heated at 100° C. for 20 minutes to obtain the FTO glass deposited with the light absorbing layer and the hole transport layer.
[0025] 2,2-Bipyridine was dissolved in chlorobenzene to obtain a 1 mg / mL passivator solution, which was spin-coated at a spin-coating speed of 2000 rpm for 30 seconds. The passivator solution was spin-coated on the FTO glass deposited with the light absorbing layer and the hole transport layer, and heated at 85° C. for 20 minutes to obtain a deposited passivation layer.
[0026] 70 mg of Spiro-OMeTAD was added to 1 mL of chlorobenzene doped with 18 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-FSI) and 30 μL of 4-tert-butylpyridine (4-tBP), and the mixture was thoroughly mixed to prepare a spiro-OMeTAD solution with a concentration of 70 mg / mL; the Spiro-OMeTAD solution was spin-coated on the passivation layer at a speed of 3000 rpm for 40 s, and then annealed at 100°C for 5 min to obtain a hole transport layer with a thickness of 100 nm.
[0027] Using vacuum coating machine, in 1×10 -5 80nm gold was evaporated under Pa as electrode to obtain perovskite solar cell.
[0028] Example 2
[0029] Prepare FTO glass with 80nm nickel oxide hole transport layer deposited on it and move it into the glove box for later use.
[0030] 2535.5 mg of PbI 2 Powder, 874.4 mg of MAI powder and 429.7 mg of dimethyl sulfoxide were dissolved in 3.5 mL of DMF and stirred for 12 min; filtered using a 0.22 μm polyethersulfone filter membrane to obtain an absorbing layer precursor solution and aged it at 60° C. for 2 h to obtain an aged absorbing layer precursor solution.
[0031] The aged light absorbing layer precursor solution is spin-coated on the FTO glass deposited with the hole transport layer, and heated at 100° C. for 20 minutes to obtain the FTO glass deposited with the light absorbing layer and the hole transport layer.
[0032] 2,2-Bipyridine was dissolved in chlorobenzene to obtain a 3 mg / mL passivator solution, which was spin-coated at a spin-coating speed of 4000 rpm for 10 seconds. The passivator solution was spin-coated on the FTO glass deposited with the light absorption layer and the hole transport layer, and heated at 85° C. for 20 minutes to obtain a deposited passivation layer.
[0033] 70 mg of Spiro-OMeTAD was added to 1 mL of chlorobenzene doped with 18 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-FSI) and 30 μL of 4-tert-butylpyridine (4-tBP), and the mixture was thoroughly mixed to prepare a spiro-OMeTAD solution with a concentration of 70 mg / mL; the Spiro-OMeTAD solution was spin-coated on the passivation layer at a speed of 3000 rpm for 40 s, and then annealed at 100°C for 5 min to obtain a hole transport layer with a thickness of 100 nm.
[0034] Using vacuum coating machine, in 1×10 -5 80nm gold was evaporated under Pa as electrode to obtain perovskite solar cell.
[0035] Example 3
[0036] Prepare FTO glass with 80nm nickel oxide hole transport layer deposited on it and move it into the glove box for later use.
[0037] 2535.5 mg of PbI 2 Powder, 874.4 mg of MAI powder and 429.7 mg of dimethyl sulfoxide were dissolved in 3.5 mL of DMF and stirred for 12 min; filtered using a 0.22 μm polyethersulfone filter membrane to obtain an absorbing layer precursor solution and aged it at 60° C. for 2 h to obtain an aged absorbing layer precursor solution.
[0038] The aged light absorbing layer precursor solution is spin-coated on the FTO glass deposited with the hole transport layer, and heated at 100° C. for 20 minutes to obtain the FTO glass deposited with the light absorbing layer and the hole transport layer.
[0039] 2,2-Bipyridine was dissolved in chlorobenzene to obtain a 5 mg / mL passivator solution, which was spin-coated at a spin-coating speed of 3000 rpm for 20 seconds. The passivator solution was spin-coated on the FTO glass deposited with the light absorbing layer and the hole transport layer, and heated at 85° C. for 20 minutes to obtain a deposited passivation layer.
[0040] 70 mg of Spiro-OMeTAD was added to 1 mL of chlorobenzene doped with 18 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-FSI) and 30 μL of 4-tert-butylpyridine (4-tBP), and the mixture was thoroughly mixed to prepare a spiro-OMeTAD solution with a concentration of 70 mg / mL; the Spiro-OMeTAD solution was spin-coated on the passivation layer at a speed of 3000 rpm for 40 s, and then annealed at 100°C for 5 min to obtain a hole transport layer with a thickness of 100 nm.
[0041] Using vacuum coating machine, in 1×10 -5 80nm gold was evaporated under Pa as electrode to obtain perovskite solar cell.
[0042] Example 4
[0043] Prepare FTO glass with 80nm nickel oxide hole transport layer deposited on it and move it into the glove box for later use.
[0044] 2535.5 mg of PbI 2 Powder, 874.4 mg of MAI powder and 429.7 mg of dimethyl sulfoxide were dissolved in 3.5 mL of DMF and stirred for 12 min; filtered using a 0.22 μm polyethersulfone filter membrane to obtain an absorbing layer precursor solution and aged it at 60° C. for 2 h to obtain an aged absorbing layer precursor solution.
[0045] The aged light absorbing layer precursor solution is spin-coated on the FTO glass deposited with the hole transport layer, and heated at 100° C. for 20 minutes to obtain the FTO glass deposited with the light absorbing layer and the hole transport layer.
[0046] 2,2-Bipyridine was dissolved in chlorobenzene to obtain a 6 mg / mL passivator solution, which was spin-coated at a spin-coating speed of 2500 rpm for 25 seconds. The passivator solution was spin-coated on the FTO glass deposited with the light absorbing layer and the hole transport layer, and heated at 85° C. for 20 minutes to obtain a deposited passivation layer.
[0047] 70 mg of Spiro-OMeTAD was added to 1 mL of chlorobenzene doped with 18 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-FSI) and 30 μL of 4-tert-butylpyridine (4-tBP), and the mixture was thoroughly mixed to prepare a spiro-OMeTAD solution with a concentration of 70 mg / mL; the Spiro-OMeTAD solution was spin-coated on the passivation layer at a speed of 3000 rpm for 40 s, and then annealed at 100°C for 5 min to obtain a hole transport layer with a thickness of 100 nm.
[0048] Using vacuum coating machine, in 1×10 -580nm gold was evaporated under Pa as electrode to obtain perovskite solar cell.
[0049] Example 5
[0050] Prepare FTO glass with 80nm nickel oxide hole transport layer deposited on it and move it into the glove box for later use.
[0051] 2535.5 mg of PbI 2 powder, 874.4 mg of MAI powder, 95 mg of DMAI powder and 429.7 mg of dimethyl sulfoxide were dissolved in 3.5 mL of DMF and stirred for 12 min; filtered using a 0.22 μm polyethersulfone filter membrane to obtain an absorbing layer precursor solution and aged it at 60° C. for 2 h to obtain an aged absorbing layer precursor solution.
[0052] The aged light absorbing layer precursor solution is spin-coated on the FTO glass deposited with the hole transport layer, and heated at 100° C. for 20 minutes to obtain the FTO glass deposited with the light absorbing layer and the hole transport layer.
[0053] 2,2-Bipyridine was dissolved in chlorobenzene to obtain a 3 mg / mL passivator solution, which was spin-coated at a spin-coating speed of 4000 rpm for 10 seconds. The passivator solution was spin-coated on the FTO glass deposited with the light absorption layer and the hole transport layer, and heated at 85° C. for 20 minutes to obtain a deposited passivation layer.
[0054] 70 mg of Spiro-OMeTAD was added to 1 mL of chlorobenzene doped with 18 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-FSI) and 30 μL of 4-tert-butylpyridine (4-tBP), and the mixture was thoroughly mixed to prepare a spiro-OMeTAD solution with a concentration of 70 mg / mL; the Spiro-OMeTAD solution was spin-coated on the passivation layer at a speed of 3000 rpm for 40 s, and then annealed at 100°C for 5 min to obtain a hole transport layer with a thickness of 100 nm.
[0055] Using vacuum coating machine, in 1×10 -5 80nm gold was evaporated under Pa as electrode to obtain perovskite solar cell.
[0056] Comparative Example 1
[0057] Prepare FTO glass with 80nm nickel oxide hole transport layer deposited on it and move it into the glove box for later use.
[0058] 2535.5 mg of PbI 2Powder, 874.4 mg of MAI powder and 429.7 mg of dimethyl sulfoxide were dissolved in 3.5 mL of DMF and stirred for 12 min; filtered using a 0.22 μm polyethersulfone filter membrane to obtain an absorbing layer precursor solution and aged it at 60° C. for 2 h to obtain an aged absorbing layer precursor solution.
[0059] The aged light absorbing layer precursor solution is spin-coated on the FTO glass deposited with the hole transport layer, and heated at 100° C. for 20 minutes to obtain the FTO glass deposited with the light absorbing layer and the hole transport layer.
[0060] 70 mg of Spiro-OMeTAD was added to 1 mL of chlorobenzene doped with 18 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-FSI) and 30 μL of 4-tert-butylpyridine (4-tBP), and the mixture was thoroughly mixed to prepare a spiro-OMeTAD solution with a concentration of 70 mg / mL; the Spiro-OMeTAD solution was spin-coated on the passivation layer at a speed of 3000 rpm for 40 s, and then annealed at 100°C for 5 min to obtain a hole transport layer with a thickness of 100 nm.
[0061] Using vacuum coating machine, in 1×10 -5 80nm gold was evaporated under Pa as electrode to obtain perovskite solar cell.
[0062] Test Example 1
[0063] After forming the passivation layer in Example 1, a scanning electron microscope test was performed. The test results are as follows: Figure 1 After forming the light absorbing layer in Comparative Example 1, a scanning electron microscope was performed, and the test results were as follows: Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that after the passivation layer is formed, the light-absorbing layer film has fewer holes, the grains are closely arranged, and the overall quality is better.
[0064] Test Example 2
[0065] The JV curves of the perovskite solar cells obtained in Examples 1 to 5 and Comparative Example 1 were measured respectively, and the open circuit voltage Voc, short circuit current Jsc, fill factor FF and photoelectric conversion efficiency PCE were determined accordingly. The JV curves were measured using a digital source meter Keithley 2400 under the conditions of simulated solar light source AM1.5G (100mW.cm-2); standard silicon cells were used for calibration before the measurement. The effective area of the device was defined by the black mask and was 0.09cm 2 The test results are shown in Table 1.
[0066]
[0067]
[0068] It can be seen from Table 1 that compared with the comparative example, the perovskite solar cells prepared in Examples 1 to 5 of the present invention have higher performance parameters of open circuit voltage Voc, short circuit current Jsc, fill factor and photoelectric conversion efficiency PCE.
[0069] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0070] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0071] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A passivation layer, characterized in that: The passivation layer is formed by spin coating a passivation agent solution, wherein the passivation agent solution comprises a passivation agent and an organic solvent, and the passivation agent is 2,2-bipyridine.
2. The passivation layer according to claim 1, characterized in that The organic solvent is chlorobenzene.
3. The passivation layer according to claim 1, characterized in that The mass volume ratio of the passivating agent to the organic solvent is (1-6) mg:1 mL.
4. The passivation layer according to claim 1, characterized in that The spin coating has a rotation speed of 2000-4000 rpm and a time of 10-30 seconds.
5. A perovskite solar cell, characterized in that: The invention comprises the passivation layer according to any one of claims 1 to 4, wherein the passivation layer is spin-coated on the light absorbing layer.
6. The perovskite solar cell according to claim 5, characterized in that The light absorbing layer is formed by a light absorbing layer precursor solution, and the light absorbing layer precursor solution includes PbI2 powder, MAI powder, dimethyl sulfoxide and an organic solvent.
7. The preparation method according to claim 6, characterized in that: The light absorbing layer precursor solution also includes DMAI powder.
8. A method for preparing a perovskite solar cell, characterized in that: The method for preparing the perovskite solar cell according to any one of claims 5 to 7 or the perovskite solar cell comprising the passivation layer according to any one of claims 1 to 4 comprises the following steps: spin coating a passivation agent solution on the light absorbing layer, and annealing to obtain the passivation layer.
9. The preparation method according to claim 8, characterized in that: The annealing time is 80-100° C. and the annealing time is 15-20 minutes.
10. Use of the perovskite solar cell according to any one of claims 5 to 7, or the perovskite solar cell comprising the passivation layer according to any one of claims 1 to 4, or the perovskite solar cell prepared by the method of claim 8 or 9 in rooftop photovoltaic systems and outdoor mobile devices.
Citation Information
Cited By
Perovskite solar cell based on pyridinium sulfide derivative passivation and preparation method thereof
CN120826146A
Perovskite light absorption layer passivation solution and application thereof
CN120897610A